PELAKU PEDOFILIA (Tinjauan Dari Faktor Penyebab dan Aspek Dinamika Psikologis) - Pambudi Rahardjo; Kaniya Puri (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to find out the psychological dynamics in pedophiles. The focus of research is the factors causing pedophile behavior in perpetrators. This study uses a qualitative method with a case study approach. The results showed that the perpetrator was a person known by the victim, namely the neighbor and the teacher. In general, the three participants have similarities in the factors causing pedophile behavior. The main common factors of the three participants in this study are the lack of affection from the family, especially the father figure, low self-esteem, failure to have a relationship with a partner, feeling disappointed or frustrated, consumption of pornographic content, and the inability to control sexual desire. Meanwhile, the different factors of the three participants were poor environment, having a less harmonious family background, relatively low level of economy, and education. Having-teen sexual experiences or have been victims of sexual harassment, having been physically abused or the victims of bullying and having sexual disorders can also be the factors. In addition, all three participants had a lack of sex education or understanding related to participants' cognitive aspects. There are also some factors related to affective aspects, namely feelings of guilt or even feeling of satisfaction after these three participants engage in inpedophile behavior. The conative aspect includes other factors such as the consumption of pornographic content, and the way participants give the lure to the victims and their threats, as well as how to perform pedophile behavior by inserting genitals into the victim's anus and then touching, pressing down the victim's genitals.